Intergenerational Transmission of Health at Birth from Mothers and Fathers - Osea Giuntella; Giulia La Mattina; Climent Quintana-Domeque (Institute of Labor Economics (IZA), 2019)
We use a unique data set of linked birth records from Florida to analyze the intergenerational transmission of health at birth by parental gender. We show that both paternal and maternal birth weights significantly predict the child's birth weight even after accounting for all genetic and environmental factors that are common and time-invariant within a family. Our estimates reveal that a one standard deviation increase in mother's birth weight (535 grams) translates into a 0.13-0.23 standard deviations increase in child's birth weight (70-123 grams), accounting or not for maternal grandmother fixed effects. On the father's side, we find that a one standard deviation increase in father's birth weight (563 grams) translates into a 0.10-0.14 standard deviations increase in child's birth weight (51-73 grams), accounting or not for maternal grandmother fixed effects. The significant role of both maternal and paternal health at birth in explaining offspring health at birth is confirmed when using alternative metrics: intrauterine growth restriction, being small for gestational age, or being too heavy (i.e., macrosomic).
Keywords: J1; 330; intergenerational transmission; health capital; birth outcomes; gender